Impact and prognosis of lung cancer in patients with combined pulmonary fibrosis and emphysema - Oh, Jee Youn; Lee, Young Seok; Min, Kyung Hoon; Hur, Gyu Young; Lee, Sung Yong; Kang, Kyung Ho; Shim, Jae Jeong (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2020)
Background: Combined pulmonary fibrosis and emphysema (CPFE) is frequently associated with lung cancer. However, the impact and outcomes of lung cancer in patients with CPFE are not clear.Objective: We, therefore, investigated the impact of lung cancer in patients with CPFE in terms of acute exacerbation (AE) and mortality, and identified the mortality predictors of patients with both CPFE and lung cancer.Methods: We retrospectively reviewed the medical records of patients at the Korea University Guro Hospital for 12 years. Based on computed tomography findings, we selected CPFE patients with and without lung cancer, and analyzed age; sex; smoking status and history in terms of pack-years; body mass index; past medical history; pulmonary function; the gender, age, and physiology (GAP) score; AE; and mortality.Results: Out of 227 CPFE patients, 61 were diagnosed with lung cancer. While 10 of the 61 patients experienced AE, 41 died during the observation period. Lung cancer was a significant predictor of AE (HR 3.27, 95% CI 1.44–7.43, P < 0.01) and mortality (HR 4.74, 95% CI 2.55–8.81, P < 0.01) in CPFE patients. AE, rather than age, GAP score, or lung cancer stage, was the most significant factor associated with mortality in patients with both CPFE and lung cancer (HR 9.20, 95% CI 1.13–74.70, P = 0.04).Conclusions: Lung cancer has a significant impact on outcomes of CPFE and is associated with severe complications. Therefore, the diagnosis and treatment of lung cancer should be carefully planned in patients with CPFE.